2010
DOI: 10.1016/j.joca.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cyclooxygenase-2 expression and prostaglandin E2 production in chondrocytes by avocado soybean unsaponifiables and epigallocatechin gallate

Abstract: The present study demonstrates that the anti-inflammatory activity of ASU and EGCG is potentiated when used in combination. This combination may offer an attractive supplement or alternative to non-steroidal anti-inflammatory drugs (NSAIDs) in the management of osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 58 publications
1
66
1
Order By: Relevance
“…Although all cells used in this study were isolated from degenerated discs, the difference in the expression of studied inflammation-related genes between the untreated control group and the EGCG-treated group is not significant, because basal expression of these genes decreases when cells are transferred to in vitro conditions (data not shown). While this is the first IVD-related study, protective effects of EGCG and green tea extract have been reported in inflammatory arthritis (Shen et al, 2012), where EGCG was shown to block IL-1β-induced expression of IL-6, IL-7, IL-8, IL-1β, TNF-α (Akhtar and Haqqi, 2011), MMP1 and MMP13 (Ahmed et al, 2004), iNOS (Singh et al, 2002) and COX-2 (Heinecke et al, 2010), and these effects were linked mostly to NF-κB and JNK signalling pathways Akhtar and Haqqi, 2011;Rasheed et al, 2009;Singh et al, 2002;Singh et al, 2003). In order to determine the underlying mechanisms in the IVD, potential pathways were identified from the literature Akhtar and Haqqi, 2011;Rasheed et al, 2009;Singh et al, 2002;Singh et al, 2003) and the effects of EGCG on IRAK-1 degradation as well as NFkB and MAPK activity in IVD cells were analysed.…”
Section: Discussionmentioning
confidence: 85%
“…Although all cells used in this study were isolated from degenerated discs, the difference in the expression of studied inflammation-related genes between the untreated control group and the EGCG-treated group is not significant, because basal expression of these genes decreases when cells are transferred to in vitro conditions (data not shown). While this is the first IVD-related study, protective effects of EGCG and green tea extract have been reported in inflammatory arthritis (Shen et al, 2012), where EGCG was shown to block IL-1β-induced expression of IL-6, IL-7, IL-8, IL-1β, TNF-α (Akhtar and Haqqi, 2011), MMP1 and MMP13 (Ahmed et al, 2004), iNOS (Singh et al, 2002) and COX-2 (Heinecke et al, 2010), and these effects were linked mostly to NF-κB and JNK signalling pathways Akhtar and Haqqi, 2011;Rasheed et al, 2009;Singh et al, 2002;Singh et al, 2003). In order to determine the underlying mechanisms in the IVD, potential pathways were identified from the literature Akhtar and Haqqi, 2011;Rasheed et al, 2009;Singh et al, 2002;Singh et al, 2003) and the effects of EGCG on IRAK-1 degradation as well as NFkB and MAPK activity in IVD cells were analysed.…”
Section: Discussionmentioning
confidence: 85%
“…Cells were seeded in flasks, and allowed to grow to confluency in control media consisting of Dulbeccos' Modified Eagle's basal medium (Sigma; St. Louis, MO, USA) supplemented with 10% v/v fetal bovine serum (Gemini Bio-Products; Woodland, CA, USA), 300 mg/ml L-glutamine (Sigma), 30 mg/ml antibiotic/antimycotic (Sigma), and 3.7 g/L sodium bicarbonate (Sigma), pH 7.4at 37°C, 5% CO 2 [9]. Chondrocytes were used at passage 2 -4.…”
Section: Treatment Designmentioning
confidence: 99%
“…Chondrocyte phenotype was characterized by immunofluorescence staining for collagen and aggrecan [9]. Chondrocytes were seeded at 1 × 10 4 cells/well on Slides were washed 3 times with PBS and nuclei were stained with DAPI (Gibco Invitrogen) for 30 minutes as described above.…”
Section: Collagen and Aggrecan Immunofluorescencementioning
confidence: 99%
See 2 more Smart Citations